IMPLEMENTASI PROGRAM KAMPUNG ANAK NEGERI KOTA SURABAYA: (Studi Pada UPTD Kampung Anak Wonorejo) - Anisah Anisah Puteri Djatmiko; Yusuf Hariyoko; Adi Soesiantoro (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
The Surabaya city government cares about the welfare of street children. In 2009 the Surabaya City Public Children's Village program was designed by the Social Service and then 3 UPTD offices were formed which included the UPTD Kampung, Kalijudan State Children's Village UPTD, Griya Werdha Home. Government communication with the perpetrators who are responsible for screening Street Children who live in the city of Surabaya. The role of the community in reducing the number of street children directly reduces poverty for the families to be accommodated. This study aims to look at the implementation of the State Children's Village Program at UPTD Wonorejo State Children's Village. The research method that the writer uses is descriptive qualitative research. And the successful implementation of the Surabaya City State Children's Village program was analyzed by the author using 4 indicators derived from Edward III's theory. 4 indicators which include Communication, Resources, Disposition, Bureaucratic structure. The results of the research analysis revealed that all assisted residents at UPTD Kampung Anak Negeri Wonorejo carry out coaching activities and activities to increase interest in talent. The emergence of problems with street children makes the authors provide suggestions for improvements to the personality of street children for the better.Abstract is the essence of the article content. It contains the summary of the whole text without taking too much detail on each part of the text.Avoid writing any acronym except it is widely known or has been stated before.